2008
DOI: 10.2527/jas.2006-814
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of copper from copper glycinate in steers fed high dietary sulfur and molybdenum1,2

Abstract: Sixty Angus (n = 29) and Angus-Sim-mental cross (n = 31) steers, averaging 9 mo of age and 277 kg of initial BW, were used in a 148-d study to determine the bioavailability of copper glycinate (CuGly) relative to feed-grade copper sulfate (CuSO(4)) when supplemented to diets high in S and Mo. Steers were blocked by weight within breed and randomly assigned to 1 of 5 treatments: 1) control (no supplemental Cu), 2) 5 mg of Cu/kg of DM from CuSO(4), 3) 10 mg of Cu/kg of DM from CuSO(4), 4) 5 mg of Cu/kg of DM fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 21 publications
5
48
0
1
Order By: Relevance
“…It is suggested that Cu supplementation increased Cu status in sheep. This is in agreement with findings in steers [16][17][18]. The higher plasma Cu concentrations with Cu supplementation in the present study are consistent with previous findings in Inner Mongolian White Cashmere goats [19] and steers [20].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…It is suggested that Cu supplementation increased Cu status in sheep. This is in agreement with findings in steers [16][17][18]. The higher plasma Cu concentrations with Cu supplementation in the present study are consistent with previous findings in Inner Mongolian White Cashmere goats [19] and steers [20].…”
Section: Discussionsupporting
confidence: 94%
“…In contrast, Eckert et al [28] reported that plasma ceruloplasmin activity in ewes was not affected by supplemental Cu. Cu status affected by Cu level (10 or 20 mg/kg) in the present study is consistent with previous results of Hansen et al [17], who observed that plasma ceruloplasmin, plasma, and liver Cu values were greater in steers supplemented with 10 mg Cu/kg DM than in those supplemented with 5 mg Cu/kg DM.…”
Section: Discussionsupporting
confidence: 93%
“…This area has 5.5 million cattle, being beef calf breeding the main activity. Production is extensive and it is sustained by natural pastures characterized by low level of Cu and excessive concentrations of iron (Fe), sulfur (S) and molybdenum (Mo), which reduces the available Cu (Mattioli 1998, Hansen et al 2008. These conditions are aggravated in association with flooded soils which increase the incidence and severity of illness (Ramirez et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…They found that 10 mg of Cu/kg of DM increased plasma and liver Cu, and concentration of Cp compared with steers supplemented with 5 mg of Cu/kg of DM. In addition, the same study demonstrated that feeding steers copper glycinate was associated with greater plasma Cp than with copper sulfate (19.0 vs. 14.6 µg/mL) (Hansen et al, 2008).…”
Section: Stage Of Lactation and Breedmentioning
confidence: 85%
“…Under normal circumstances the hepatic Cu pool is not rate-limiting for holo-Cp synthesis, as concentration of Cp in the serum concentration increases rapidly during infection, trauma, and pregnancy while the ratio of apo-to holo-Cp is maintained (Matsuda et al, 1974). The basal oxidase activity of Cp in the plasma of female Angus calves, Holstein dairy cows, and steers (Angus and Angus x Simmental) was estimated at 1.31, 60, and 21.9 µg/mL, respectively (Cerone et al, 2000, Hansen et al, 2008, Nazifi et al, 2009; whereas the basal concentration of Cu was approximately 0.75 and 1.14 µg/mL in calves and steers, respectively (Cerone et al, 2000, Hansen et al, 2008. A recent study of Hussein et al (2011) reported concentrations of Cp in the serum of dairy cows during different stages of lactation (3-1 wk prepartum; 0-1 wk; 3-5 wk, and 15-18 wk postpartum) and showed greater concentration during 0-1 wk postpartum.…”
Section: Stage Of Lactation and Breedmentioning
confidence: 99%